Gait cycle profile in individuals with non-specific low back pain - I Komang Rama; Kinandana , Gede Parta; Widnyana, M. (PT. Kesehatan Gerak Fungsi Tubuh, 2025)
Background: Lower Back Pain (LBP) is a frequently reported global health issue, LPB can cause biomechanical disturbances in the gait cycle, including reduced speed, increased step asymmetry, and postural stability disturbances, which can increase the risk of falls and decrease the quality of life of the sufferers. This review aimed to explore changes in the gait cycle in individuals with LBP compared to those without LBP, focusing on biomechanical aspects such as spatiotemporal and kinetic parameters. Methods: This study uses a literature review method. Articles were searched through Pubmed and Google Scholar using the keywords